Penerapan Pembelajaran Pendidikan Kewarganegaraan Melalui Penguatan P5 Dalam Meningkatkan Keahlian Bernalar Kritis Siswa - Sunaryati, Titin; Sentana, Maria; Listiani, Marissa Eva; Apriliani, Ardini; Septiani, Mawar (LP2M Universitas Islam Ahmad Dahlan, 2024)
This investigation conducted a comprehensive Literature Review from multiple sources like scientific publications, books, and studies that analyze the effectiveness of PPKn learning through enhanced P5's role is to enhance the critical thinking abilities of elementary school students. Through the lens of critical theory various empirical investigations, this investigation revealed consistent trends, patterns, and findings regarding the effectiveness of P5. The findings of the investigation indicate that P5 has the potential to be a powerful base for creating. its effectiveness in inspiring students to think critically, but its success is primarily based on the innovative design of learning assistance from the school's environment, and active participation by students. This investigation suggests that it's necessary to additional research to investigate the potential of P5 in a larger learning context.